Language Rules of Interpretation and Ushul Fiqh and their Application in A Global Context - Budi Afriandi; Hengki Ras Bumi; Ahmad Roisuddin Ritonga; Mursal Mursal; Abdul Halim Hanafi (Yayasan Adra Karima Hubbi, 2025)
Background. In the global context, understanding the holy texts of the Qur'an and the application of Islamic law face increasingly complex challenges, especially related to language qaedah, tafsir qaedah, and ushul fiqh. Purpose. This research aims to explore the relationship between linguistic qaedah, tafsir qaedah, and ushul fiqh, as well as identifying effective strategies for applying these three aspects in the context of modern life. Method. This study uses a qualitative method with a literature study approach through analysis of relevant literature related to interpretation and ushul fiqh. Results. The results of the study show that language rules play an important role in determining the meaning and context of the verses of the Qur'an, which then influences the process of interpretation and legal decision-making in ushul fiqh. Conclusion. the application of the principles of maqashid al-syari'ah and qawaid fiqhiyyah in interpretation can enrich understanding and increase the relevance of Islamic law in the modern era.